Determination of ammonia chloride acute toxicity for a region specific fish species (Hyphessobrycon callistus) - Murilo Damato; Edison Barbieri (O Mundo da Saúde, 2011)
Ecotoxicological assays have been used as an important tool in the evaluation of environmental quality. With the objective to emphasize the relevance of the use of native organisms in short-duration chronic assays, this study evaluated the potential of Hyphessobrycon callistus. Static tests were carried through exposing adult organisms to the following concentrations of Ammonia Chloride (NH4Cl): 0.5; 0.75; 1.0; 1.5; 2.0; e 2.5 mg.L-1. The sensitivity response was about 3 to 4 times lesser than that of assays reported in the literature. This way, complementary studies are necessary to establish the optimal conditions of exposition and to verify the possibility of a more sensible subletal effect.